Australian perspective regarding recommendations for physical activity and exercise rehabilitation in pulmonary arterial hypertension - Fowler, R.; Jenkins, Susan; Maiorana, Andrew; Gain, Kevin; O'Driscoll, G.; Gabbay, Eli (Dove Medical Press Ltd, 2011)
Aim: To determine the opinion of health care professionals within Australia, regarding acceptable levels of exertion and symptoms, and referral for exercise rehabilitation in patients with pulmonary arterial hypertension (PAH). Method: In 2010, 76 health care professionals at a specialist pulmonary hypertension meeting in Australia were surveyed using a self-administered questionnaire. The questionnaire included case studies of patients with PAH in World Health Organization (WHO) functional classes II–IV. For each case study, respondents were asked to report their opinion regarding the acceptable level of exertion and symptoms during daily activities, and whether they would refer the patient for exercise rehabilitation. Three additional questions asked about advice in relation to four specific physical activities. Results: The response rate was 70% (n = 53). Overall, 58% of respondents recommended patients undertake daily activities 'as tolerated'. There was no consensus regarding acceptable levels of breathlessness or fatigue, but the majority of respondents considered patients should have no chest pain (73%) and no more than mild light-headedness (92%) during daily activities. Overall, 63% of respondents would have referred patients for exercise rehabilitation. There was little difference in opinion regarding the acceptable level of exertion or symptoms, or referral for exercise rehabilitation, according to functional class. However, the patients' functional class did influence the advice given regarding the specific physical activities. Conclusion: In 2010, there were inconsistencies between individual health care professionals within Australia regarding appropriate levels of physical exertion and acceptable symptoms during daily activities. Almost two-thirds of the respondents reported they would refer patients for exercise rehabilitation.